Partisipasi Masyarakat dalam Pelaksanaan Musyawarah Perencanaan Pembangunan (Musrembangdes): Studi Tentang Musrembangdes di Desa Tapobali, Kecamatan Adonara Timur, Kabupaten Flores Timur Tahun 2022 - Safika Plewan Bura; Esrah D.N.A Benu; Frans B. Ricky Humau (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The aim of this research is to determine community participation in the implementation of development planning deliberations (Musrembangdes) and determine the inhibiting factors that influence the lack of community participation in Tapobali Village, East Adonara District in 2022. This research is a descriptive qualitative research with research locations in Tapobali Village, Adonara District East, East Flores Regency. The theory used in this research is the Community Participation Theory from Isbandi (2007:27) and in this theory there are four forms of participation according to Vaneklasen and Miller, in which there are indicators of Symbolic Participation, Passive Participation, Consultative Participation and Functional Participation. Researchers used data collection methods in this research obtained through observation, interviews and documentation. Researchers found that the level of community participation in Musrembangdes in Tapobali Village was still low. 55 people attended the Musrembangdes, but the residents who attended also tended to contribute minimally to ideas regarding village development planning. It is hoped that the village government will further increase community participation in village development programs so that it can bring optimal benefits to all village residents.